Influence of Organizational Culture and Empowerment correlated to Work Engagement As an Intervening Variables towards to the Serivice Quality of General Bureau at the Ministry of State Secretariat - Wibowo; Koko Haryono; Henry Eryanto (Journal of Business and Behavioural Entrepreneurship, 2021)
The aim of this research is to reveal the effect of organizational culture and empowerment correlated to work engagement as an intervening variable in relations to general affairs quality serviceability in term of directly nor indirectly, as well as considering the adjusted strategy to enhance serviceability quality. This research uses survey method in quantitative research. The sum of this research is depicted from staff members of General Affairs at The Indonesian Foreign Affairs of The Republic of Indonesia. It is denoted as N = 307 staffs using Slovin Theory obtained n = 76. The technique in analyzing data used SPSS and LISREL. In the result of the research revealed that (1) the culture of an organization has a direct impact towards the quality of a service, (2) empowerment gives a direct positive impact on service quality, (3) work bonding also gives a positive reaction on a quality of a service, (4) moreover, an organizational culture response a straight positive outcome on a network, (5) empowerment also give a straightforward outcome on work bondage, (6) culture of an organization also gives a direct impact on empowerment, (7 ) the culture of an organization through empowerment results a positive impact on service quality, (8) culture of an organization through a work bondage gives a positive effect on service quality at General Affairs at The Indonesian Foreign Affairs of The Republic of Indonesia. Based on a hypothetical analysis it was discovered that an organizational culture has a high encounter on a service quality of 0,323 or 32,3%. Whereas a variable indirect impact resulted organizational culture had no direct impact on service quality through empowerment with the value of 0,509 or 50,9%. This result will be used as a testimony for the institution in order to maintain as well as elevate and expand the dimension and it’s indicator I order to increase service quality of General Affair’s staffs. Thus, can be concluded that in order to generate an optimal service quality among staffs, an organization necessitates to manufacture and uplift organizational culture, empowerment and work bond among the staffs.